Ion Channel Expression and Characterization in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Zhao, Zhihan (Stem Cells Int, 2018)
BACKGROUND: Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are providing new possibilities for the biological study, cell therapies, and drug discovery. However, the ion channel expression and functions as well as regulations in hiPSC-CMs still need to be fully characterized. METHODS: Cardiomyocytes were derived from hiPS cells that were generated from two healthy donors. qPCR and patch clamp techniques were used for the study. RESULTS: In addition to the reported ion channels, I(Na), I(Ca-L), I(Ca-T), I(f), I(NCX), I(K1), I(to), I(Kr), I(Ks) I(KATP), I(K-pH), I(SK1–3), and I(SK4), we detected both the expression and currents of ACh-activated (KACh) and Na(+)-activated (KNa) K(+), volume-regulated and calcium-activated (Cl-Ca) Cl(−), and TRPV channels. All the detected ion currents except I(K1), I(KACh), I(SK), I(KNa), and TRPV1 currents contribute to AP duration. Isoprenaline increased I(Ca-L), I(f), and I(Ks) but reduced I(Na) and I(NCX), without an effect on I(to), I(K1), I(SK1–3), I(KATP), I(Kr), I(SK4), I(KNa), I(Cl-Ca), and I(TRPV1). Carbachol alone showed no effect on the tested ion channel currents. CONCLUSION: Our data demonstrate that most ion channels, which are present in healthy or diseased cardiomyocytes, exist in hiPSC-CMs. Some of them contribute to action potential performance and are regulated by adrenergic stimulation.